A psychological reaction of higher education students to the new national exit exam in the case of Dilla University, 2023 - Kassaw, Chalachew; Demareva, Valeriia; Getu, Samrawit; Negash, Misrak; Alemayehu, Selamawit (Frontiers in Psychology, 2024)
Introduction: Test anxiety is an emotional state characterized by physiological and behavioral responses linked to the fear of poor exam results. performane. It can result in a significant impact in the ItIt can significantly affect the overall academic achievement of . students. Addressing the contributing factors of the problem is better to intervene in the academic challenges of students and creative a conducive learning environment. Thus, Thisthis study investigated the association between test anxiety and the newly implemented national exit exam program among prospective graduate students at Dilla University in 2023. Methods: A community-based cross-sectional design was employed, involving 357 participants recruited from August 15 to September 14, 2023. Data collection utilized structured questionnaires combined with interviews. The Westside Test Anxiety Inventory (WTAI) assessed test anxiety levels. Epi Info version 7 facilitated data entry, with subsequent analysis conducted using SPSS version 25. A p-value < 0.05 was used to determine statistical significance in the multivariate logistic regression model.The prevalence of test anxiety associated with the national exit exam among prospective graduates at Dilla University was 68.9% (95% CI: 63.9%-73.7%). The analysis identified significant associations between test anxiety and several factors: non-formal educational background of parents (AOR = 2.84, 95% CI: 2.12-4.65), moderate social support (AOR = 0.24, 95% CI: 0.12-0.46), and poor coping mechanisms (AOR = 3.67, 95% CI: 2.45-5.67).This study revealed a substantial prevalence of test anxiety among graduating students in relation to about the national exit exam. The findings suggest that factors such as limited social support and inadequate coping mechanisms contribute to test anxiety. Targeted interventions, including social support programs, counseling services, coping mechanism training, parental education, and support for students with lower academic performance, may be beneficial in mitigating test anxiety.